A new molecular understanding of the thermal degradation of PA 66 doped with metal oxides: Experiment and computation. (October 2015) - Duemichen, E.; Braun, U.; Sturm, H.; Kraemer, R.; Deglmann, P.; Gaan, S.; Senz, R.
Abstract: The thermal molecular degradation of polyamide 66 (PA 66) doped with (partially supported) metal oxide particles (Fe2 O3, ZnO, Al2 O3 ) was investigated qualitatively and quantitatively using common analysis techniques like thermogravimetry coupled with IR-spectroscopic evolved gas analysis (TGA-FTIR). Using pyrolysis coupled with gas chromatography mass spectrometry (Py-GC-MS), qualitative conclusions were drawn about the complex hydrocarbon products. However, the combination of TGA with solid-phase extraction, followed by thermal desorption gas chromatography mass spectrometry (TED-GC-MS), allows qualitative and even semi-quantitative conclusions about the decomposition pathway of PA 66 in the presence of various metal oxide particles. The investigations under inert conditions showed that the presence of metal particles increases the rate of decarboxylation and deamination reactions, as well as the formation rate of cyclopentanone and pyridine derivatives. These species are a consequence of various condensation reactions. The condensation reactions release a large amount of water, thus triggering the hydrolysis of PA 66. Molecular thermal degradation mechanisms were developed for the main decomposition as well as for the condensation reactions and supported by quantum chemical calculations. The catalytic effect of the metal oxides in PA 66 increases in the following order: PA 66 = PA 66 – Al2 O3 < PA 66 – Fe2 O3 < PA 66 – ZnO.